**I. Solve the following differential equations:**

**Question 1.**

Solution:

**Question 2.**

**Question 3.Solution:**

**Question 4.**

Substituting these values in (1), we get

**Question 5.Solution:**

**Question 6.Solution:**

**Question 7.Solution:**

**Question 8.Solution:**

**Question 9.Solution:**

**Question 10.Solution:**

**Question 11.x dy + 2y · dx = 0, when x = 2, y = 1Solution:**

∴ x dy + 2y · dx = 0

∴ x dy = -2y dx

Integrating, we get

This is the general solution.

When x = 2, y = 1, we get

4(1) = c

∴ c = 4

**Question 13.**

**Question 14.**